Dairy farmers’ knowledge and practices in silage-making Vis-a-Vis assessment of silage quality and silo structures at field level in Punjab (India) - Kajalpreet Kaur; Singh, Jaswinder; Jaspal Singh Hundal; Chadda, Akshita; Rajesh Kasrija; Paviter Kaur (Indian Journal of Dairy Science, 2026)
This research examines the knowledge and practices of dairy farmers regarding silage production, along with the silage quality and silo structures in the Punjab (India). Data on knowledge, practices, and silo structures were collected from 385 silage-making farmers, selected through multistage sampling techniques across the state using a pre-tested and structured interview schedule. A total of 100 silage samples were examined for quality characteristics and Flieg score, and 18 samples were tested for mycotoxin levels. The results highlighted that 52.72% of farmers had a medium level of knowledge and practice score. The majority of farmers prepared silage on their own (84.42%), lined the bottom of the silo with tarpaulin, straw, or both (85.5%), covered the silo from the top immediately after compaction (74.03%), fed the silage round the year (81.56%), removed silage from the silo manually on a daily basis (84.94%), and were unaware about silage additives (79.74%). The knowledge-practice score was positively correlated (p < 0.01) with herd size (r = 0.185), milk production (r = 0.159), land owned (r = 0.125), and training attended (r = 0.626). The average dry matter, pH, crude protein, lactic acid, and ammonia nitrogen were 29.52±1.30%, 4.34±0.94, 9.36±0.88%, 4.34±0.58%, and 9.82±2.3%, respectively. The average Flieg score of silage was 90.58±36.82, indicating good quality. The mean mycotoxin level was 18.49±16.0 ppb (range 2.10 - 50). The majority of respondents (n=275) had pit silos while the rest of the 110 farmers had stacked silos. The average dimensions (length x breadth x depth) of the silo were 59.07 x 17.74 x 3.08 feet. Around 21% of participants reported challenges in silage-making, while 28% faced issues with silage feeding. The research identified the areas of silage production that require greater attention from researchers and extension service agencies to enhance the knowledge and practices of dairy farmers.